2018
DOI: 10.1002/bit.26784
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte‐like cells generated by direct reprogramming from murine somatic cells can repopulate decellularized livers

Abstract: Direct reprogramming represents an easy technique to generate induced hepatocytes (iHeps) from somatic cells. However, current protocols are accompanied by several drawbacks as iHeps are heterogenous and lack fully mature phenotypes of primary hepatocytes. Here, we established a polycistronic expression system to induce the direct reprogramming of mouse embryonic fibroblasts towards hepatocytes. The resulting iHeps are homogenous and display key properties of primary hepatocytes, such as expression of hepatocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Studies investigating whether this approach is feasible are lacking. Several studies have successfully achieved reendothelialization (with or without coating the remaining ECM) and parenchymatous recellularization of liver scaffolds in vitro [8,20,64,73,112,113,[116][117][118][119][120][121][122][123]. Various cell types, such as hepatocytes (e.g.…”
Section: Livermentioning
confidence: 99%
“…Studies investigating whether this approach is feasible are lacking. Several studies have successfully achieved reendothelialization (with or without coating the remaining ECM) and parenchymatous recellularization of liver scaffolds in vitro [8,20,64,73,112,113,[116][117][118][119][120][121][122][123]. Various cell types, such as hepatocytes (e.g.…”
Section: Livermentioning
confidence: 99%
“…Mechanistic mouse studies show that the activation of the Activin / Nodal – EOMES loop turns on the high levels of canonical TFs that control hepatogenesis in the mouse embryo. This includes Gata6 and Gata4 (Zhao et al, 2005), Foxa2 and Foxa1 (Lee et al, 2005), which have been implicated in pioneering chromatin remodeling in foregut precursors (Zaret and Carroll, 2011), and were utilized in the induction of hepatocyte transdifferentiation (Chen et al, 2018; Wamaitha et al, 2015). Moreover, Gata4 and Gata6 were shown to be functionally redundant in promoting the development of the liver, and together with Foxa2 they promote liver specification by inducing Hhex (Denson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, expandable through several scale-up cultivation protocols, iHeps can be used as a source for drug discovery and screening [1012]. Chen and colleague demonstrated that iHeps repopulate a decellularized liver disc [16]. In this study, the decellularized liver provides an optimal microenvironment for in vitro maturation of iHeps.…”
Section: Introductionmentioning
confidence: 89%